Uji Signifikansi Pengaruh Kreativitas Belajar pada Keterampilan Membaca Siswa - Urip Widodo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of student learning creativity on reading ability. The research method used is an ex-post-facto quantitative approach. The subjects of this study were Buddhist students of class VII in Pagentan District, totaling 22 people. The results showed that the significance value obtained was 0.00. As for the consequences of data analysis, the contribution of learning creativity to reading ability is 59.5%. In conclusion, there is a significant effect between learning creativity and reading the text of Gautama Buddha's biography in English. Keywords: Learning Creativity, Quantitative, Reading